2016
DOI: 10.1186/s13030-016-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire survey regarding the support needed by Yogo teachers to take care of students suspected of having eating disorders (second report)

Abstract: BackgroundThe lowering of the age of onset and chronicity have been key problems related to eating disorders (EDs). As the proportion of teens in the estimated onset ages has increased, it has become important to detect students with EDs and to clarify how they can be supported. Though epidemiological surveys of Yogo teachers (school nurse/health science teachers) have been conducted to inquire about the number of such students, none of these were done according to ED type based on DSM-5. Thus, we conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The recent questionnaire survey of children and youth in schools revealed high rates of suspected cases of BN and binge eating disorders (BED) among adolescents, but there were few chances to access special treatment services due to the hesitation of the patients as well as the lack of available delivery services in EDs in the community [ 23 ]. A way of providing support in the community should be required, as the proportion of teens at the estimated onset age of EDs has increased year by year in Japan [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…The recent questionnaire survey of children and youth in schools revealed high rates of suspected cases of BN and binge eating disorders (BED) among adolescents, but there were few chances to access special treatment services due to the hesitation of the patients as well as the lack of available delivery services in EDs in the community [ 23 ]. A way of providing support in the community should be required, as the proportion of teens at the estimated onset age of EDs has increased year by year in Japan [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, despite findings from the national report conducted in 2014–15 indicating low annual incidence rates of BED and no cases of ARFID at hospitals, teachers working with children and adolescents (e.g., elementary school–high school) have reported encountering multiple cases of ARFID and BED amongst their pupils during this time (Seike et al, 2016, 2016). This suggests that patients with these disorders avoid professional help or that clinicians in hospitals are unaware of these disorders in Japan.…”
Section: Resultsmentioning
confidence: 97%
“…Potential participants were provided with a link to a web‐based survey in the information letter, with the survey and study database maintained using Research Electronic Data Capture (REDCap; Harris et al, 2009), which was hosted by the BC Children's Hospital Research Institute. Given the high proportion of participants in previous studies who have reported a lack of familiarity with the diagnosis of ARFID (Katzman et al, 2014; Seike et al, 2016), to reduce selection bias study recruitment materials did not include the term ARFID, and instead referred to a survey about familiarity with challenges relating to “picky eating”, and experiences in working with children and youth who may struggle with feeding or nutrition, or have anxiety related to food or eating. This wording was employed to include clinical presentations that the participants outside of specialized feeding or eating disorder programs may have encountered.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study of Yogo teachers in Japan (health educators who are also responsible for weighing students and reviewing medical records to screen for medical concerns) found that 13.0% of Yogo teachers had encountered youth with symptoms consistent with ARFID. The majority of Yogo teachers indicated they had limited knowledge about ARFID—58.8% reported not knowing the diagnosis well, and 15.4% reported not knowing anything about the diagnosis (Seike et al, 2016). In contrast, less than 1% of the sample reported an absence of knowledge concerning the diagnosis of anorexia nervosa (AN) or bulimia nervosa (BN), suggesting a discrepancy in knowledge across ED diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation